Suzanne Fleischman & Linda R. Waugh (eds.), Discourse pragmatics and the verb. Routledge, London, 1991; 220 pp. - Jurado Salinas, Martha (El Colegio de México, 1993)
Se reseñó el libro: Discourse pragmatics and the verb.